Newman et la conscience dans son roman Callista et dans son sermon « Ce qui dispose à la foi » - Michel Durand (Cahiers Victoriens et Edouardiens)
The ‘astonishing variety of literary genres’ to which Newman turned his hand must not blind us to the underlying unity of all his work. His two novels are thus not mere diversions but form an integral part of his overall vision. The article examines Newman’s skills (and occasional weaknesses) as a novelist, the (relative) value of his historical tableaux and, most importantly, the autobiographical content and the religious dimension of each, in particular Callista (1856). Whilst Loss and Gain (1848) can in no way be described as autobiographical it certainly contains, alongside the author’s brilliant satire of Oxford at the time of the Tractarian Movement, elements of his own experience of conversion to Catholicism. Callista offers an even richer source of insight into the mind of the author. Whilst a number of theological themes emerge which give the novel an apologetic dimension—the authority of the Church, the importance of the priesthood, the nature of evil and sin, the importance of the liturgy and the significance of martyrdom amongst others—the key theme of the novel, and its chief centre of interest, is to be found in the theme of conversion—this time to Christianity itself—and the role played by conscience in this process, as illustrated in the character of the young Greek pagan, Callista.